The role of the informal sector in poverty alleviation : An empirical investigation with reference to greater Wad Medani locality of the Gezira State, Sudan - Muhmode, Hysum; Mohamed, Adam (Gezira Journal of Agricultural Science, 2010)
This study investigated the role of the informal sector in poverty alleviation in Sudan with reference to Wad Medani Locality of the Gezira State in January 2008. The data for the study was collected by means of a questionnaire, which was distributed to a random cluster sample of 80 households working in the informal sector in the study area. To examine the impact of the informal sector in poverty alleviation, the "before and after" approach was adopted where data on the relevant variables were analyzed for two periods, before and after joining the informal sector. Income and expenditure were used separately as indicators of welfare. The Lorenz curve and Gini coefficient were used as measures of income and expenditure inequality. The three standard poverty indices were also calculated, namely incidence, depth, and severity of poverty. The results suggested that the income and expenditure distribution after working in the informal sector was more equitable than before joining the sector. With regard to poverty measures, the results suggested that 92% of the households in the sample fell below the income poverty line before working in the sector compared to 70% after working in the sector, while 94% and 60% of households fell below the expenditure poverty line before and after joining the sector, respectively. Thus, income and expenditure poverty was found to be more prevalent among the sample of households before working in the sector. Similar results were also obtained for the depth and severity of poverty, where income and expenditure poverty were deeper and more severe before joining the sector. These results indicated the important role of the informal sector in reducing inequality and alleviating poverty.     تقصت هذه الدراسة دور القطاع غير الرسمي في التخفيف من وطأة الفقر بمحلية واد مدني الكبرى بولاية الجزيرة بالسودان . لهذا الغرض، استخدم الاستبيان كوسيلة لجمع البيانات من عينة عشوائية عنقودية تتكون من 80 أسرة تعمل في القطاع غير الرسمي في منطقة الدراسة. لأغراض التعرف على تأثير العمل بالقطاع غير الرسمي على الفقر، استخدمت الطريقة القبلية والبعدية، حيث جمعت البيانات لأفراد العينة حول متغيرات الدراسة لفترتين: الأولى قبل العمل بالقطاع غير الرسمي ، والثانية بعد العمل بذلك القطاع. استخدم الدخل والأنفاق كمؤشرين للمستوى المعيشي للأسرة، كما استخدم منحنى لورنز ومعامل جينى لقياس عدم العدالة في توزيع الدخل والأنفاق. أما  فيما يختص بمؤشرات الفقر، فقد استخدمت الصيغ الثلاث المعروفة لقياس حدوث الفقر، عمق الفقر، وحدة الفقر استناداً على الدخل والإنفاق كمؤشرين للرفاه.أشارت النتائج الإحصائية إلى أن توزيع الدخل والأنفاق بعد العمل في القطاع غير الرسمي أكثر عدالة منه قبل العمل في هذا  القطاع. فيما يتعلق بتأثير العمل بالقطاع غير الرسمي على الفقر، أشارت النتائج إلى أن 92% من الأسر بعينة الدراسة يقعون تحت خط الفقر على أساس الدخل قبل العمل بالقطاع غير الرسمي، بينما 70% يقعون تحت خط الفقر على أساس الدخل أيضاً بعد العمل بالقطاع غير الرسمي. كذلك أشارت الدراسة إلى نتائج مماثلة تستند إلى خط الفقر على أساس الإنفاق، حيث لوحظ أن 94% من الأسرة يقعون تحت خط الفقر على أساس الإنفاق قبل العمل بالقطاع غير الرسمي، بينما 60% من الأسر يقعون تحت خط الفقر بعد العمل بالقطاع غير الرسمي. توضح هذه النتائج أن الفقر على أساس الدخل والإنفاق كان أكثر انتشاراً وسط الأسر بعينة الدراسة قبل العمل في القطاع غير الرسمي مقارنة بحالة الفقر بعد العمل بذلك القطاع. كذلك تشير الدراسة إلى نتائج مماثلة فيما يختص بعمق وحدة الفقر على أساس الدخل والإنفاق، حيث لوحظ أن الفقر أكثر عمقا وحدة قبل الارتباط بالقطاع غير الرسمي مقارنة بالحالة بعد العمل بذلك القطاع. تفضي هذه النتائج إلى تأكيد أهمية الدور الكبير الذي يمكن أن يلعبه  القطاع غير الرسمي في التخفيف من وطأة الفقر وتعزيز العدالة في توزيع الدخل.